Exploring the Influence of Knowledge and Sharia Financial Literacy on Student Preferences for Indonesian Islamic Banks - Suganda, Dedi Atmi (Universitas Proklamasi 45, 2025)
The low level of Islamic financial literacy in Indonesia, including among university students, is a major challenge in increasing Islamic financial inclusion in Indonesia. Although the Islamic finance industry is growing, students' understanding of Sharia-based principles and services, such as Bank Syariah Indonesia (BSI), is still limited. This study analyzes the influence of Islamic financial knowledge and literacy on the decision of UIN Raden Fatah Palembang students to utilize BSI services. The method used is mixed with sequential explanatory design, combining multiple linear regression, in-depth interviews, and systematic review. The results showed that Islamic financial knowledge and literacy have a significant effect on student decisions. Factors such as the Fiqh Muamalah and Islamic Economics curricula, as well as the supportive attitude of the lecturers, contribute to improving students' understanding. Active learning, such as flipped classrooms, is also effective in strengthening understanding. Social media and technology play an important role in improving Islamic financial literacy, with the utilization of films, advertisements, and character actors and influencers being very influential in introducing Islamic financial products and improving corporate image and public trust. KKN students can contribute by conducting workshops and training for community education. Supportive policies and an adaptive organizational culture are needed for wider access to digital financial services and more effective teaching.